Anti-MAG neuropathy: historical aspects, clinical-pathological correlations, and considerations for future therapeutical trials - Latov, Norman; Brannagan, Thomas H., III; Sander, Howard W.; Gondim, Francisco de Assis Aquino (Arquivos de Neuro-Psiquiatria, 2024)
Background Patients with anti-MAG neuropathy present with distal demyelinating polyneuropathy, IgM monoclonal gammopathy, and elevated titers of anti-MAG antibodies.Objective This paper reviews what is known about the clinical presentation, course, pathophysiology, and treatment of anti-MAG neuropathy, with considerations for the design of therapeutic trials.Methods A literature review of the medical and scientific literature related to anti-MAG neuropathy, and the design of therapeutic clinical trials in peripheral neuropathy.Results Anti-MAG neuropathy can remain indolent for many years but then enter a progressive phase. Highly elevated antibody titers are diagnostic, but intermediate titers can also occur in chronic inflammatory demyelinating polyneuropathy (CIDP). The peripheral nerves can become inexcitable, thereby masking the demyelinating abnormalities. There is good evidence that the anti-MAG antibodies cause neuropathy. Reduction of the autoantibody concentration by agents that target B-cells was reported to result in clinical improvement in case series and uncontrolled trials, but not in controlled clinical trials, probably due to inadequate trial design.Conclusion We propose that therapeutic trials for anti-MAG neuropathy include patients with the typical presentation, some degree of weakness, highly elevated anti-MAG antibody titers, and at least one nerve exhibiting demyelinating range abnormalities. Treatment with one or a combination of anti-B-cell agents would aim at reducing the autoantibody concentration by at least 60%. A trial duration of 2 years may be required to show efficacy. The neuropathy impairment score of the lower extremities (NIS-LL) plus the Lower Limb Function (LLF) score would be a suitable primary outcome measure.
Keywords: Demyelinating Diseases; Anti-MAG; Neuropathy